Peningkatan Kapasitas Guru dalam Mengembangkan Media Pembelajaran Information and Communication Technology (ICT) di Madrasah Ibtidaiyah Thoriqul Huda Randuharjo Pungging Mojokerto - Nadhifah Nadhifah; Imam Muslih (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2017)
The development of information and communication technology are now pervasive in many areas of life, is also in the field of education. In this regard teachers as educators have an obligation to recognize or technological literacy in learning activities. This obligation is intended to further improve the ability and skills to operate a medium of learning in order not to fall behind in the development of information. The capacity of teachers in implementing the learning process required to better utilize existing facilities. Similarly, in the media, teachers are expected to use learning media information and communication technology (ICT) so that the learning process is readily accepted by learners. The conditions found in the majority of teachers in Government Elementary School (MI) Thoriqul Huda Randuharjo Pungging District of Mojokerto in developing learning media is not maximized. This encourages this devotion to study and try to provide solutions through the development of training activities based learning media information and communication technology (ICT). With training and mentoring are expected to improve the capacity of teachers to develop instructional media-based information and communication technology (ICT). The strategic steps to be taken in the process of implementing service programs in the field of education are: Preliminary Study; Focus Group Discussion (FGD); Preparation of the Action Plan; ICT learning media development training; Mentoring action; Reflection - Action Service - Recommendations. This assistance activities provides the following results: the teachers involved in the process of intensive ICT training which plays an active role during the training and mentoring; teachers train in ICT-based learning media microsoft office powerpoint and macromedia flash; and teachers practice teaching media ICT in the learning process in low grade and high grade in MI Thoriqul Huda Randuharjo. While students in grade of 2nd MI lowly grade and high grade ie Grade of 5th MI in the learning activities are actively involved in the learning process and are more receptive to learning materials.